2019
DOI: 10.1080/09670262.2019.1628307
|View full text |Cite
|
Sign up to set email alerts
|

Six new epibioticProschkinia(Bacillariophyta) species and new insights into the genus phylogeny

Abstract: The diatom genus Proschkinia is a common element of biofilms covering diverse substrata in saline inland or shallow coastal environments. It can be distinguished from other naviculoid taxa by its lanceolate valves with a fistula located within the central area and numerous open girdle bands with a U-shaped cross-section and a single row of perforations on the internal side of the fold. Despite this distinct morphology, frustules of Proschkinia are typically weakly silicified and often overlooked when cleaned d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…each other, but in general, maintaining a good separation among the different localities. Croatian samples showed the lowest group homogeneity, with the main group of three samples and a single group comprised of one sample(CRO-13) and one sample placed in a different cluster (CRO 19). An additional nMDS analysis performed only on the Greek carapace and skin samples showed good separation of the two groups (Fig 5B).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…each other, but in general, maintaining a good separation among the different localities. Croatian samples showed the lowest group homogeneity, with the main group of three samples and a single group comprised of one sample(CRO-13) and one sample placed in a different cluster (CRO 19). An additional nMDS analysis performed only on the Greek carapace and skin samples showed good separation of the two groups (Fig 5B).…”
Section: Plos Onementioning
confidence: 99%
“…These taxa have not yet been found in epizoic samples from other localities and substrata. Similarly, the newly described Proschkinia species such as P. vergostriata Frankovich et al and P. sulcata Majewska et al have so far only been found on turtle carapaces and skin [19]. Thus, more sampling and analyses of marine benthic diatom communities from both biotic (including marine animals) and abiotic substrata will be necessary to determine the exact habitat preferences of these diatoms.…”
Section: Plos Onementioning
confidence: 99%
“…Especially since the other diagnositic features for Delicatophycus such as dorsiventral valves, areola foramina showing an undulated pattern (at least in part of their course), the steep inflexion of the raphe branches towards the ventral side approaching the middle of the valve, the dorsally deflected terminal raphe fissures and the absence of apical pore fields, fit entirely with the genus description. The presence of longitudinal ribs on the valve face and mantle is an uncommon feature in diatoms and only found in a few diatom genera: Proschkinia (Round et al 1990;Majewska et al 2019), Navicula (Sabbe et al 2019), Haslea (Simonsen 1974), Craticula (Lange-Bertalot 2001), Pinnularia (Lange-Bertalot et al 2003) and Navigiolum (Lange-Bertalot et al 2009). Two Stauroneis species, S. stodderi Greenleaf and S. staurolineata Reimer both possess very fine longitudinal ridges, running parallel from apex to apex (Patrick & Reimer 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, diatoms associated with the Mediterranean loggerhead sea turtle population have been described. These included an Olifantiella species ( Kaleli et al, 2018 ) and six new species of Proschkinia ( Majewska et al, 2019 ), and a small celled Catenula taxon from the Adriatic Sea ( Robert, Bosak & Van de Vijver, 2019 ).…”
Section: Introductionmentioning
confidence: 99%